Czy potrzeba nam szczególnej formy organizacyjno-prawnej dla innowacyjnego biznesu? Uwagi ogólne na podstawie uzasadnienia projektu prostej spółki akcyjnej — PSA - Wiórek, Piotr Marcin (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The aim of this article is a critical evaluation of the general part of the explanation of the “Recommendations concerning the project of provisions regulating the simple stock corporation prepared by a team of experts appointed by the Minister of Development and Finance (proposals for amendments of The Commercial Companies Code)”. The analysis carried out in the article leads to the conclusion that the explanation of the SSC bill does not achieve its principal goal, which should be a convincing justification for introduction of a new type of corporation into Polish commercial law system in form of the SSC. What is more: from the whole argumentation used in the explanation follows that there is no real need for such a complicated regulation as planned, and the proposed provisions go far beyond the goals which the regulation wants to achieve. Moreover, they are inadequate to achieve these goals
Keywords: simple stock corporation; rules of legislative technique; startup; inventor; corporation